Millennial variations in atmospheric CO2 during the early Holocene (11.7–7.4 ka) - J. Shin; J. Shin; J. Ahn; J. Chowdhry Beeman; H.-G. Lee; J. M. Seo; E. J. Brook (Climate of the Past, 2022)
We present a new high-resolution record of atmospheric CO2 from the Siple Dome ice core, Antarctica, over the early Holocene (11.7–7.4 ka) that quantifies natural CO2 variability on millennial timescales under interglacial climate conditions. Atmospheric CO2 decreased by ∼10 ppm between 11.3 and 7.3 ka. The decrease was punctuated by local minima at 11.1, 10.1, 9.1, and 8.3 ka with an amplitude of 2–4 ppm. Although the explanations of carbon cycle mechanisms remain uncertain due to insufficient paleoclimate records and model simulations, these variations correlate with proxies for solar forcing and local climate in the southeast Atlantic polar front, eastern equatorial Pacific, and North Atlantic. Additional CO2 measurements using better-quality ice cores and carbon cycle models are needed to confirm the observation.